Editorial 2.2 - Carter, H. (Journal of University Teaching and Learning Practice, 2005)
It is a pleasure to see papers covering such a broad range of teaching and learning issues being submitted to the Journal. Some of these might challenge our conceptions of what constitutes teaching and learning practice but where possible we try to be inclusive of these ideas. Welcome to the second issue of volume two of the Journal of University Teaching and Learning Practice.